Assessing a late truth commission: challenges and achievements of the Brazilian National Truth Commission - Torelly, Marcelo (International journal of transitional justice, 2018)
Mobilizing the literature, official documents, press materials and field notes, this article discusses the Brazilian National Truth Commission (NTC) timing, process and results. It argues that Brazil’s transitional justice evolved differently from that of its neighbouring countries and that establishing the truth was just one of the NTC’s goals. Created when much of the truth was known, the Brazilian NTC had to address two competing expectations: first, the promotion of an account of the past that supported the previously established conciliatory narrative (the status quo expectation); and second, to challenge that path by mobilizing society against impunity (the victims’ expectation). This tension influenced the NTC’s agenda and its results. Despite the modest outcomes in truth seeking, the NTC achieved three main goals: improving historical accountability; promoting international human rights norms; and challenging the veto power that the military still holds. This constitutes a step forward.